PERENCANAAN PRODUKSI SEPATU BAHAN KAIN TENUN DI MEDALI MAS BANDAR KEDIRI - Heribertus Budi Santosa; Lolyka Dewi Indrasari; Ana Komari; Afiff Yudha Tripariyanto (Prodi Teknik Industri S1 Institut Teknologi Nasional Malang, 2022)
Production activities always involve a budget that is not small. The better efficient it is done, the less the budget will be spent. This research aims to find out the target number of requests. , and target minimum profit . The research location is MSME Weaving Ikat Medali Mas Kediri. The analysis method uses 3 priorities to include targets of demand, production costs and profit with an overall goal with the function . Analysis using the methods of Linear Trend Regression and Goal Programming. Based on the results of the study, forecasting demand in 2021 amounted to 2281 pairs. Function cannot achieve the target demand with an optimum solution of 418,930 pairs, while the Min Z = d_4 ^ + function can achieve the target production cost with an optimum solution of Rp. 765,046,918 and function Can achieve the profit target with an optimum solution of Rp. 454,923,577